2011
DOI: 10.3324/haematol.2011.040535
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of EVI1 is associated with epigenetic alterations and good prognosis in patients with acute myeloid leukemia

Abstract: The online version of this article has a Supplementary Appendix. BackgroundThe EVI1 gene (3q26) codes for a zinc finger transcription factor with important roles in both mammalian development and leukemogenesis. Over-expression of EVI1 through either 3q26 rearrangements, MLL fusions, or other unknown mechanisms confers a poor prognosis in acute myeloid leukemia. Design and MethodsWe analyzed the prevalence and prognostic impact of EVI1 over-expression in a series of 476 patients with acute myeloid leukemia, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…However, as with other members of the TGF-b family, there is evidence to suggest that GDF15 turns from a tumor suppressor to a tumor promoter in the course of carcinogenesis. 64,65 The data presented in this report imply EVI1, a developmental regulator and an oncogene involved in a variety of tumors, [2][3][4][5][13][14][15][16]66,70 and ATRA as novel regulators of GDF15 in both haematopoietic and epithelial cells, and show that GDF15 is required for the reinforcing effect of EVI1 on ATRA induced cell cycle arrest. In addition to providing new information about the regulation and function of this clinically highly relevant cytokine, these results suggest that cooperative interactions between EVI1 and ATRA are not restricted to haematopoietic cells.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, as with other members of the TGF-b family, there is evidence to suggest that GDF15 turns from a tumor suppressor to a tumor promoter in the course of carcinogenesis. 64,65 The data presented in this report imply EVI1, a developmental regulator and an oncogene involved in a variety of tumors, [2][3][4][5][13][14][15][16]66,70 and ATRA as novel regulators of GDF15 in both haematopoietic and epithelial cells, and show that GDF15 is required for the reinforcing effect of EVI1 on ATRA induced cell cycle arrest. In addition to providing new information about the regulation and function of this clinically highly relevant cytokine, these results suggest that cooperative interactions between EVI1 and ATRA are not restricted to haematopoietic cells.…”
Section: Discussionmentioning
confidence: 58%
“…[2][3][4][5] EVI1 overexpression has also been observed in variable proportions of patients with myelodysplastic syndromes (MDS), [6][7][8] chronic myeloid leukemia (CML), [9][10][11] acute lymphoblastic leukemia (ALL), 12 and certain epithelial tumors. [13][14][15][16] An association between elevated EVI1 mRNA levels and poor prognosis is particularly well documented for AML, [2][3][4][5]17,18 but has also been reported for other malignancies. 8,10,13,14 Corroborating its role as an oncogene capable of initiating malignant transformation, in a human gene therapy trial for chronic granulomatous disease clones with activating integrations of the therapeutic vector into the EVI1 locus expanded preferentially, followed by evolution into MDS and, ultimately, AML.…”
Section: Introductionmentioning
confidence: 99%
“…Hidemasa Matsuo, 1 Mio Kajihara, 1 Daisuke Tomizawa,2 Tomoyuki Watanabe, 3 Akiko Moriya Saito,4 Junichiro Fujimoto, 5 Keizo Horibe, 4 Kumi Kodama, 1 Mayu Tokumasu, 6 Hiroshi Itoh, 1 Hideki Nakayama, 7 Akitoshi Kinoshita, 8 Takashi Taga, 9 Akio Tawa, 10 Tomohiko Taki, 11 Norio Shiba, 12 Kentaro Ohki, 13 Yasuhide Hayashi, 13 Yuka Yamashita, 14 Akira Shimada,…”
Section: Evi1mentioning
confidence: 99%
“…However, the prognostic value of EVI1 overexpression has been studied mostly in adult AML. [5][6][7][8][9] Only two studies have examined EVI1 overexpression in pediatric AML, but a detailed analysis according to the type of leukemia was not performed because of the small sample size.…”
mentioning
confidence: 99%
“…When survival curves were analyzed in the AML group with ages ranging from 14 to 60 years, all of them treated with similar chemotherapy schemes, no significant difference was observed. However, a recent collaboration with other groups, showed that EVI1 overexpression is a poor prognostic marker in patients <65 years in an independent large cohort, and showed that the total absence of EVI1 expression has a prognostic impact in the outcome of acute myeloid leukemia patients (Vazquez et al,2011).…”
Section: Evi1 Overexpressionmentioning
confidence: 99%